No biotic homogenisation across decades but consistent effects of landscape position and pH on macrophyte communities in boreal lakes. Issue 2 (22nd October 2019) - Lindholm, Marja; Alahuhta, Janne; Heino, Jani; Toivonen, Heikki
Abstract : It has been predicted that spatial beta diversity shows a decreasing trend in the Anthropocene due to increasing human impact, causing biotic homogenisation. We aimed to discover if vascular aquatic macrophyte communities show different spatial patterns in beta diversity in relation to land use and environmental characteristics in different decades from 1940s to 2010s. We aimed to discover if spatial structures differ between species‐, phylogeny‐ and functional‐based beta diversity. We used presence–absence data of aquatic macrophytes from five decades from small boreal lakes. We utilized generalised dissimilarity modelling to analyse spatial patterns in beta diversity in relation to environmental gradients. We found that lake elevation and pH were the most important variables in each decade, while land use was not particularly important in shaping beta diversity patterns. We did not find signs of a decreasing trend in spatial beta diversity in our study area during the past 70 yr. We did not find signs of either biotic homogenisation or biotic differentiation (taxonomic, phylogenetic or functional). Vascular aquatic macrophyte communities showed only slightly different beta diversity patterns in relation to human impact across decades. The patterns of different facets of beta diversity diverged only slightly from each other. Lake position in the landscape, reflecting both natural connectivity and lake characteristics, explained the patterns found in beta diversity, probably because our study area has faced only modest changes in land use from 1940s to 2010s when compared globally. Our study highlights the fact that biotic homogenisation is not an unambiguous process acting similarly at all spatial and temporal scales or in different environments and different organism groups.